Protective role of nitric oxide in mice with Shiga toxin-induced hemolytic uremic syndrome - Dran, Graciela Isabel (2002)
Background : Nitric oxide (NO) is an endogenous vasodilator and platelet inhibitor. An enhanced NO production has been detected in patients with hemolytic uremic syndrome (HUS), although its implication in HUS pathogenesis has not been clarified. Methods : A mouse model of Shiga toxin 2 (Stx2)-induced HUS was used to study the role of NO in the development of the disease. Modulation of L-arginine-NO pathway was achieved by oral administration of NO synthase (NOS) substrate or inhibitors, and renal damage, mortality and platelet activity were evaluated. The involvement of platelets was studied by means of a specific anti-platelet antibody. Results : Inhibition of NO generation by the NOS inhibitor L-NAME enhanced Stx2-mediated renal damage and lethality; this effect was prevented by the addition of L-arginine. The worsening effect of L-NAME involved enhanced Stx2-mediated platelet activation, and it was completely prevented by platelet depletion. Conclusions : NO exerts a protective role in the early pathogenesis of HUS, and its inhibition potentiates renal damage and mortality through a mechanism involving enhanced platelet activation.